Expanding life’s radius?: Evaluating geolocation data of women with posttraumatic stress disorder related to childhood abuse throughout a randomized controlled trial - Rehder, Johanna; Guth, Marvin; Ebner-Priemer, Ulrich; Kleindienst, Nikolaus; Priebe, Kathlen; Müller-Engelmann, Meike; Friedmann, Franziska; Rausch, Sophie; Bohus, Martin; Fydrich, Thomas; Steil, Regina; Santangelo, Philip (Journal of psychopathology and clinical science, 2025)
Experiences of childhood abuse often relate to reduced physical and mental well-being in adulthood, affecting the everyday life behavior of people with posttraumatic stress disorder (PTSD) after childhood abuse. Passive sensing via digital sensors allows for examining manifestations of psychopathology, for example, restricted activity space, in daily life. However, there is a scarcity of research applying this method in therapy research. Building on previous cross-sectional findings showing restricted activity space in PTSD, we used global positioning system (GPS) tracking in a randomized controlled trial (RCT) to examine how treatment effects of two treatment arms, dialectical behavior therapy for PTSD (DBT-PTSD) and cognitive processing therapy (CPT), map to changes in patients’ daily lives throughout 12 months of outpatient psychotherapy. We examined the spatial and temporal activity spaces of women with PTSD (n = 166, Mage = 35.81, SDage = 10.98) at three timepoints over the course of 1 week each: pretreatment (t1RCT), 6 months into treatment (t3RCT), and at the end of the intensive treatment phase after 12 months (t5RCT). While both DBT-PTSD and CPT have demonstrated efficacy in treating PTSD with affective instability, with DBT-PTSD showing superiority over CPT, these effects did not transfer to the everyday life activity spaces captured via GPS tracking. Comparing t1RCT to t5RCT, linear mixed models revealed no effect of timepoint or treatment on movement radius and time spent away from home. Hence, previously reported treatment effects were not reflected in GPS data. While patients reported decreased symptom severity their behavioral data still show restricted activity space in daily life. (PsycInfo Database Record (c) 2025 APA, all rights reserved)
Gesehen am 16.09.2025